Transitions across cognitive states and death among older adults in relation to education: A multistate survival model using data from six longitudinal studies. Issue 4 (3rd February 2018) - Robitaille, Annie; van den Hout, Ardo; Machado, Robson J.M.; Bennett, David A.; Čukić, Iva; Deary, Ian J.; Hofer, Scott M.; Hoogendijk, Emiel O.; Huisman, Martijn; Johansson, Boo; Koval, Andriy V.; van der Noordt, Maaike; et al.
Abstract: Introduction: This study examines the role of educational attainment, an indicator of cognitive reserve, on transitions in later life between cognitive states (normal Mini‐Mental State Examination (MMSE), mild MMSE impairment, and severe MMSE impairment) and death. Methods: Analysis of six international longitudinal studies was performed using a coordinated approach. Multistate survival models were used to estimate the transition patterns via different cognitive states. Life expectancies were estimated. Results: Across most studies, a higher level of education was associated with a lower risk of transitioning from normal MMSE to mild MMSE impairment but was not associated with other transitions. Those with higher levels of education and socioeconomic status had longer nonimpaired life expectancies. Discussion: This study highlights the importance of education in later life and that early life experiences can delay later compromised cognitive health. This study also demonstrates the feasibility and benefit in conducting coordinated analysis across multiple studies to validate findings. Highlights: There are benefits to coordinated analysis across multiple longitudinal studies. Education and socioeconomic status delays the progression to mild cognitive impairment. Higher education and socioeconomic status increases noncognitively impaired life expectancy.